Hubungan antara Kompetensi Guru dan Penggunaan Pembelajaran Deep Learning Pendekatan Pedagogik: Analisis PLS-SEM - Benyamin Jago Belalawe; James Adam Seo (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the relationship between teacher competence—covering pedagogical, professional, social, and personal dimensions—and the use of deep learning conceptualized as a deep approach to learning that fosters critical thinking, creativity, collaboration, and communication. Situated within the broader discourse on 21st-century education, this research addresses the limited empirical evidence explaining how multidimensional teacher competence predicts the implementation of deep pedagogical approaches. The study involved 25 teachers, encompassing eight variables and 32 indicators. The analytical procedure employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4, conducted through outer and inner model evaluations, including convergent validity, discriminant validity, construct reliability, and bootstrapping-based hypothesis testing. The findings indicate that not all aspects of teacher competence exert a direct influence on each dimension of soft skills. However, pedagogical, professional, and personal competencies significantly contribute to strengthening critical thinking and creativity among teachers and students. These results underscore the strategic role of teacher professional development in advancing deep pedagogical practices and provide policy-relevant insights for strengthening teacher competence frameworks in contemporary education systems.